Bioethical aspects of control and application of pest control substances in Chile - Muñoz Quezada, María Teresa (Acta Bioethica, 2011)
In Chile, pest control substances selling and application is increasing, and although there are regulations about importation, commercialization, control and application, these are not effective in the regulation of their use by the population, mainly no occupational. Chilean Senate rejected a bill which prohibits the use of pest control substances considered highly dangerous worldly, what has led to strong claims of nongovernmental organizations and agricultural communities exposed to these toxics, highlighting errors in the legislation process for agro chemists and lack of information about effects and risks of toxicity, mainly chronic for those exposed to pest control substances. This study discuss the scarce bioethics concern by authorities and citizens about the effects being generated by pest control substances in the population and the environment, revealed in the continuity of commercialization and application of highly toxic pest control substances, and in the presence of pest control residues in vegetable products commercialize at national level.